Changes of Phenolic Contents and Antioxidant Activity in Soybean Seeds Harvested from Phakopsora pachyrhizi Infected Crops - Eriyanto Yusnawan; Novita Nugrahaeni; Joko Susilo Utomo (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Asian soybean rust caused by Phakopsora pachyrhizi is one of the most destructive foliar diseases on soybean. Severe infection of this disease causes early defoliation and reduces the yield. To determine the response of soybean genotypes to this disease and the changes of metabolites in seeds, a greenhouse study was conducted using eight Indonesian soybean cultivars, i.e. Malabar, Wilis, Ringgit, Pangrango, Argomulyo, Grobogan, Dena 1, and Dena 2. The experiment was arranged in a randomized completely block design and repeated three times. The soybean crops were inoculated with the pathogen and another set was not inoculated. Infection of P. pachyrhizi reduced fresh biomass, seed weight per plant, and weight of 100 seeds. However, total flavonoid contents in seeds increased from 12 to 50% in all infected genotypes. The increase of daidzein from 27 to 67% in seeds was observed, except for Malabar and Argomulyo . The increase of genistein was genotypic dependence. The increase of total phenolic contents as well as antioxidant activity was also depending on the genotypes. P. pachyrhizi could be one of the biotic elicitors to increase total flavonoid contents in soybean seeds. Dena 1 less suffered from the rust infection as represented by the least pustule number, less reduction in seed weight and weight of 100 seeds. Secondary metabolites particularly phenolics and isoflavones in seeds of this cultivar increased significantly after the rust infection. This cultivar could be considered as an alternative tolerant genotype where cultivated area is favorable for soybean rust infection.